FEATURES OF THE ORGANIZATION OF FINANCIAL ACCOUNTING AT THE PRESENT STAGE - G. V. Goliguzova (Дискурс, 2018)
The article addresses the issues of goals, objectives and place of the financial accounting system of a commercial organization at the present stage. It is assumed that financial accounting is a subsystem of business accounting and is governed by the current legislation of the Russian Federation on accounting. The main purpose of organizing a financial accounting system is to provide sufficient and reliable information to external users of financial statements. Each external user of the information received from the financial statements of a commercial organization solves specific problems, and each representative from the designated circle of external users should be provided with comprehensive characteristics of the state of financial and economic activities of the commercial organization. These issues are resolved in the framework of reforming the entire accounting system. The feature of the modern stage of economic relations development is that, firstly, the reform processes both of the accounting system in general and of financial accounting system are accelerated, and secondly, the general public, represented by legal entities and all interested individuals is involved in the development of normative legislative acts.